Developing an empirical Environmental Kuznets Curve - Ferry Purnawan; Akhmad Fauzi; Sahat M. H. Simanjuntak (Economic Journal of Emerging Markets, 2015)
This study aims to develop a model of Environmental Kuznets Curve (EKC) that relates between environmental pollution level and the prosperity level in Tangerang City. The method uses two models of pooled data regression technique namely, Random Effect Model (REM), and Fixed Effects Model (FEM) both quadratic and cubic. The period of observation is 2002-2012. The results suggest that relationship between per capita income and the level of environment quality, reflected as the BOD concentration (Oxygen Biological damage) and COD (Chemical Oxygen Damage) can be explained by the quadratic FEM model and follow the EKC hypothesis even though the turning point is not identified.